Information, pesticide safety behaviors, and toxicity risk perceptions: Evidence from Zambia and Mozambique - Goeb, Joseph; Smart, Jenny; Snyder, Jason; Tschirley, David (International Food Policy Research Institute, 2022)
Purpose: Pesticide safety is a growing global concern particularly in developing countries as farmers increase their use of toxic pesticides that can negatively affect farmer and environmental health. Previous literature recommends improving farmer access to information to boost productivity, sustainability, and safety behaviors but has little to say on which information sources have the greatest impacts. This paper explores the relationships between information from different sources and toxicity knowledge and safety behaviors using an innovative metric of exposure.